Principles of international environmental law - Sands, Philippe , 1960-; Fabra Aguilar, Adriana; MacKenzie, Ruth , 1964-; Peel, Jacqueline , 1974- (Cambridge University Press, 2012)
The third edition of this classic text offers comprehensive and critical commentary on international environmental law